Herpes Simplex Virus Protocols - Brown, S. Moira; MacLean, Alasdair R.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 1998)
Herpes Simplex Virus Protocols comprises a wide range of experimental protocols that should be especially useful to new workers in herpes virology. Hopefully, it will also provide information for those with experience in the field, as well as those embarking on techniques that are new to them. Obviously the range of topics covered cannot be comprehensive, but we have tried to provide protocols dealing with those procedures that are most widely used; and we have selected expert authors accordingly. We have also tried to cover the range from the more biological in vivo maneuvers to purely molecular procedures, taking into account the topical interest in the potential use of HSV as a therapeutic tool. In this way there should be sufficient inf- mation for most procedures the average herpes virologist is likely to require-- at least at this moment in time! Since the herpesviruses are a large family, we have largely based the protocols on the virus we know best--herpes simplex virus. With this as the prototype, it should be relatively easy to extrapolate and make the necessary modifications required for application to some of the other herpesviruses, especially members of the alpha group, such as PRV and EHV. It would have been an impossible task to include chapters covering the unique aspects of each known herpesvirus.
HSV Growth, Preparation, and Assay -- HSV Entry and Spread -- Preparation of HSV-DNA and Production of Infectious Virus -- HSV Mutagenesis -- Saturating Mutagenesis and Characterization of a Herpesvirus Genome Using In Vivo Reconstitution of Virus from Cloned Subgenomic Regions -- Construction and Use of Cell Lines Expressing HSV Genes -- Analysis of HSV Polypeptides -- Protein Purification -- Expression and Purification of Secreted Forms of HSV Glycoproteins from Baculovirus-Infected Insect Cells -- Crystallization of Macromolecules for Three-Dimensional Structure Determination -- Direct Immunogold Labeling of Herpesvirus Suspensions -- Expression of HSV Proteins in Bacteria -- In Vitro Systems to Analyze HSV Transcript Processing -- Analysis of HSV-1 Transcripts by RNA-PCR -- Transient Assays for HSV Origin and Replication Protein Function -- HSV Amplicons in Gene Therapy -- Analyses of HSV Proteins for Posttranslational Modifications and Enzyme Functions -- HSV-Cellular Protein Interactions -- Models of Recurrent Infection with HSV in the Skin and Eye of the Mouse -- Pathogenesis and Molecular Biology of HSV Latency and Ocular Reactivation in the Rabbit -- HSV Latency In Vitro -- Assessing Cell-Mediated Immune Responses to HSV in Murine Systems -- Assays for HSV Gene Expression During Establishment and Maintenance of Latent Infection -- Analysis of HSV-DNA and RNA Using the Polymerase Chain Reaction -- HSV Vectors for Gene Therapy -- Investigation of the Anti-HSV Activity of Candidate Antiviral Agents.
Keywords: Microbiology; Microbiology